An Options-Based Model Of Career Mobility in Professional Service Firms - Malos, Stanley B.; Campion, Michael A. (Academy of Management Review, 1995)
Contemporary career mobility models do not fully explain up-or-out promotional systems in professional service firms (PSFs). We propose a PSF career mobility model, which represents hiring decisions as investments in options on future human capital acquisitions and promotions as exercise of those options. Promotional outcomes depend mainly on the development of employee's human capital and business conditions at the time of partnership consideration. The model explains seemingly paradoxical firm behavior, such as dismissal of nonpromoted but productive employees.